Bio-inspired synthesis of flower shaped iron oxide nanoparticles (FeONPs) using phytochemicals of Solanum lycopersicum leaf extract for biomedical applications. (August 2020) - Bharathi, Devaraj; Preethi, Selvaraj; Abarna, Kalimuthu; Nithyasri, Manjunathan; Kishore, Palaniswamy; Deepika, Kathirvel
Abstract: The synthesis of iron based magnetic nanoparticles is an expanding research area due to their potential applications in the development of novel technologies. The present study reports an eco-friendly synthesis of iron oxide nanoparticles (FeONPs) using Solanum lycopersicum leaf extract by a bio-inspired method. Synthesized FeONPs were characterized by using UV–visible spectroscopy, fourier transform infrared spectroscopy (FTIR), field emission-scanning electron microscopy (FE-SEM), energy dispersive X-ray spectroscopy (EDS) and dynamic light scattering (DLS) analysis. The formation of brownish black color and UV–visible absorbance peak at 254 nm confirmed the biosynthesis of FeONPs. The observed bands around 400-600 cm −1 in the FTIR spectrum indicated the formation of metal-oxygen (Fe–O) bond. FE-SEM images revealed the agglomeration of FeONPs having predominant flower shaped structure. EDS confirmed the presence of Fe and O elements. The mean average particles size of synthesized FeONPs was calculated to be 483.8 nm by DLS analysis. The synthesized FeONPs showed potential disc diffusion antibacterial activity against Escherichia coli and it was further confirmed by using fluorescence microscopy. The FeONPs showed significant in vitro anticancer activity against human lung cancer cell line A549 and their IC50 value was found to be 69 ± 0.50 μg/mL. In addition, acridine orange/ethidium bromide (AO/EtBr) dual fluorescent staining assay revealed the apoptosis induction property of synthesized FeONPs. Thus, the obtained results indicated that the biosynthesized FeONPs using S. lycopersicum can be used as a potential biocidal nanomaterials in biomedical sectors. Highlights: Iron oxide nanoparticles (FeONPs) were synthesized using S. lycopersicum by a bio-inspired method. FeONPs were characterized by using UV–visible spectroscopy, FTIR, FE-SEM, EDS and DLS techniques. Synthesized FeONPs exhibited potential antibacterial and anticancer activity.